A narrative review of cost-effectiveness analysis of people living with HIV treated with HAART: from interventions to outcomes - Tse WF; Yang W; Huang W (Dove Medical Press, 2015)
Wah Fung Tse,1 Weimin Yang,2 Wenlong Huang1,3 1School of International Pharmaceutical Business, China Pharmaceutical University, 2Editorial Department of Journal of Nanjing University of Traditional Chinese Medicine, Nanjing University of Chinese Medicine, 3Center of Drug Discovery, State Key Laboratory of Natural Medicines, China Pharmaceutical University, Nanjing, People's Republic of China Background: Since its introduction in 1996, highly active antiretroviral therapy (HAART), which involves the combination of antiretroviral drugs, has resulted in significant improvements in the morbidity, mortality, and life expectancy of HIV-infected patients. Numerous studies of the cost-effectiveness of HAART from different perspectives in HIV have been reported.Aim: To investigate the economic outcomes and relevance of HAART for people living with HIV.Materials and methods: A narrative literature review was conducted on 22 peer-reviewed full economic evaluations of people living with HIV treated with different HAART regimens and published in English between January 2005 and December 2014. Information regarding study details, such as interventions, outcomes, and modeling methods, was extracted. The high heterogeneity of the included studies rendered a meta-analysis inappropriate; therefore, we conducted a comparative analysis of studies grouped according to the similarity of the different intervention types and outcomes.Results: Most of the economic evaluations of HAART focused on comparisons between the specific HAART regimens and others from the following perspectives: injecting drug users versus noninjecting drug users, HIV-infected adults without AIDS versus those with AIDS, regimens based on developed world guidelines versus those based on developing world guidelines, self-administered HAART versus directly observed HAART, and “ideal” versus “typical” regimens.Conclusion: In general, HAART is more cost-effective than other therapeutic regimens adopted so far. Further investigations, especially head-to-head comparisons of “ideal” and “typical” trials of different regimen combinations, are required to identify the optimal HAART regimens. Keywords: narrative review, cost-effectiveness, HAART